Initial validation of a self-report measure of the extent of and reasons for medication nonadherence - Voils, Corrine I; Maciejewski, Matthew L; Hoyle, Rick H; Reeve, Bryce B; Gallagher, Patrick; Bryson, Christopher L; Yancy, Jr, William S (Medical care, 2012)
Self-report measures of medication nonadherence confound the extent of and reasons for medication nonadherence. Each construct is assessed with a different type of psychometric model, which dictates how to establish reliability and validity. To evaluate the psychometric properties of a self-report measure of medication nonadherence that assesses separately the extent of nonadherence and reasons for nonadherence. Cross-sectional survey involving the new measure and comparison measures to establish convergent, discriminant, and predictive validity. The new measure was readministered 2-21 days later. A total of 202 veterans with treated hypertension were recruited from the Durham Veterans Affairs Medical Center. A new self-report measure assessed the extent of nonadherence and reasons for nonadherence. Comparison measures included self-reported medication self-efficacy, beliefs about medications, impression management, conscientiousness, habit strength, and an existing nonadherence measure. Three items assessing the extent of nonadherence produced reliable scores for this sample, α = 0.84 (95% confidence interval, 0.80-0.87). Correlations with comparison measures provided evidence of convergent and discriminant validity. Correlations with systolic ( r = 0.27, P < 0.0001) and diastolic (r = 0.27, P < 0.0001) blood pressure provided evidence of predictive validity. Reasons for nonadherence were assessed with 21 independent items. Intraclass correlations were 0.58 for the extent score and ranged from 0.07 to 0.64 for the reasons. The dual conceptualization of medication nonadherence allowed a stronger evaluation of the reliability and validity than was previously possible with measures that confounded these 2 constructs. Measurement of self-reported nonadherence consistent with psychometric principles will enable reliable, valid evaluation of interventions to reduce nonadherence.